Association between thyroid function and disease severity in restless legs syndrome - Geng, Chaofan; Yang, Zhenzhen; Kong, Xiumei; Xu, Pengfei; Zhang, Hongju (Frontiers in Neurology, 2022)
Background: Restless Legs Syndrome (RLS) is a common neurological disorder. Growing evidence shows that dopaminergic dysfunction and iron deficiency are associated with the pathogenesis of RLS. Additionally, the dopaminergic system is linked with the hypothalamic- pituitary-thyroid (HPT) axis. Thus, the current study aimed to compare thyroid function between RLS patients and healthy subjects and to investigate the associations with clinical characteristics of RLS. Methods: Serum levels of thyroid hormones were investigated in 102 first-episode drug-naïve RLS patients and 80 matched healthy controls (HCs). Baseline data and clinical characteristics were performed by professional personnel. In addition, multivariate regression was used to analyze the relationship between thyroid function and RLS. Results: Compared with control group, RLS patients had significantly higher serum thyroid- stimulating hormone (TSH) levels (p ˂ 0.001), and higher prevalence of subclinical hypothyroidism (Odds ratio (OR) 8.00; 95% confidence interval (CI) = 3.50-18.30; p < 0.001). Regression analysis revealed that serum TSH (OR = 1.77; 95%CI = 1.41–2.23; p < 0.001) was independently associated with RLS. There was a statistically significant positive correlation between TSH and the Pittsburgh sleep quality index (PSQI) scores (r = 0.728, p < 0.001), and the International Restless Legs Scales (IRLS) points (r = 0.627, p ˂ 0.001). Spearman correlation analysis showed that FT3 was positive correlated with HAMA14 score (r = 0.239, p = 0.015). In addition, compared with the non-sleep disorder (NSD) group, sleep disorder (SD) patients had significantly higher serum TSH levels (p ˂ 0.001). Conclusion: Serum levels of TSH and the prevalence of subclinical hypothyroidism were higher in RLS patients, indicating the imbalance between thyroid hormones (TH) and the dopaminergic system may contribute to the development of primary RLS. Additionally, the TH axis may influence the quality of sleep in RLS patients.